Senkatana - Mofokeng, Sophonia Machabe,Mahase, Mike (Wits University Press, 2021)
Senkatana is a Sesotho play based on a Basotho legend about a monster that swallowed all the people and animals except for one pregnant woman. She gave birth to a boy, Senkatana, when a young man, killed the monster. The grateful people made him their king, but soon after he was killed to settle a family score. Senkatana is a tragic play adapted from Sotho folk narrative. The play is regarded as a classic of Sesotho literature. Seen as one of the greatest essayists and dramatists writing in Southern Sotho, Senkatana was Mofokeng's first book, published in 1952 in the African (then Bantu) Treasury Series, an imprint of Witwatersrand University Press
Description based on publisher supplied metadata and other sources
Keywords: Sotho literature; Electronic books; Drama; Théâtre